Síndrome de burn out académico en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Rodriguez Amasifuen, Maria Elena (2023)
The general objective was to determine the level of academic burnout syndrome in initial education students of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon in Iquitos in 2021. For this reason, the type of burnout was considered. descriptive research, accompanied by a cross-sectional, univariate and field design. The study population, as well as the sample, had 122 initial education students. To obtain the data, an instrument on burnout was used, which was contextualized and validated by expert judgment and the technique for obtaining the aforementioned was the survey. As a conclusion of the research, the academic burnout syndrome in initial education students of the Faculty of Educational Sciences and Humanities at the National University of the Peruvian Amazon is found in 41.8% at the low level; 39.3% at the moderate level and 18.9% at the high level. In other words, the risk of increasing the burnout syndrome is feasible if the dimensions that are at the moderate level are not improved.